2f-3g+5g-6f=

Simple and best practice solution for 2f-3g+5g-6f= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2f-3g+5g-6f= equation:


Simplifying
2f + -3g + 5g + -6f = 0

Reorder the terms:
2f + -6f + -3g + 5g = 0

Combine like terms: 2f + -6f = -4f
-4f + -3g + 5g = 0

Combine like terms: -3g + 5g = 2g
-4f + 2g = 0

Solving
-4f + 2g = 0

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '-2g' to each side of the equation.
-4f + 2g + -2g = 0 + -2g

Combine like terms: 2g + -2g = 0
-4f + 0 = 0 + -2g
-4f = 0 + -2g
Remove the zero:
-4f = -2g

Divide each side by '-4'.
f = 0.5g

Simplifying
f = 0.5g

See similar equations:

| a+6b+a+5c= | | 3[5-3(5-t)]-5=5[3(5t-5)+10]-45 | | s(x)=.5x^2-8x+34 | | 3(y+2)=16*2y | | 2c+19=45 | | b^2x^2-5bx+4=0 | | x-0.7=1.9 | | -(5y+3)-(-4y-8)=2 | | -5p=250 | | 5p=250 | | x=0.2x+40000 | | -6y=-32 | | 5(10-10x)=-5(-4x+4) | | -7y=30 | | -17+20-3=5x | | -8-8p=10-3p | | 2(a-4)=4a-2a+4 | | -5y=25 | | 4x+40+6x=1-8x+3 | | 9+10=1 | | -3x=20 | | 50-3xr=17 | | .5(t+7)=39 | | -4y=-36 | | 2(7-x)=14x+2 | | Z^2=169 | | 33.3(x+6)=7 | | x^2+8x-19=0 | | 7y=-49 | | 2r^2+19r+45=0 | | 4t-8x+2t= | | 3z-1=5-4z |

Equations solver categories